High expression of CD9 and Epidermal Growth Factor Receptor promotes the development of tongue cancer - Suhasini, P. C.; Bhat, Vadisha; Shetty, Shilpa S; Shetty, Praveen Kumar; Roopashree, P. G.; Kumari, N. Suchetha (Medical oncology (Northwood, London, England), 2024)
Tongue cancer is distinguished by aggressive behavior, a high risk of recurrence, lymph, and distant metastases. Hypoxia-Induced Factor 1 α functions as a CD9 transcription factor. CD9 is a transmembrane protein that may be found on the cell membrane. It can modulate the expression of the Epidermal Growth Factor Receptor (EGFR) pathway. ELISA was used to measure serum CD9, p-EGFR, and p-Akt levels in 70 tongue cancer patients and 35 healthy controls. RT-PCR was used to analyze the gene expression of the related genes. The gene as well as protein expression of CD9, EGFR /p-EGFR, and Akt /p-Akt was significantly higher in case subjects when compared with the controls. The expression of CD9 was higher in case subjects who were smokers/alcoholics when to control subjects who were smokers/alcoholics. Overexpression of CD9 due to hypoxic conditions leads to the activation of EGFR-signaling pathway resulting in cancer progression, resistance to chemotherapy. Hence, CD9 could be a potential target to suppress cancer progression.